The Influence Of PER, PBV, ROA, And ROE On Stock Prices (Case Study On Companies Listed In The IDX Value 30 Index For The Period February-August 2024) - Muhammad Roni Indarto; Farizki, Alfin Nizam (JURNAL ILMU MANAJEMEN, 2025)
This study aims to analyze the effect of Price Earnings Ratio (PER), Price to Book Value (PBV), Return on Assets (ROA), and Return on Equity (ROE) on stock prices of companies listed on the IDX Value 30 Index for the period February–August 2024. The selection of this index is based on the characteristics of stocks with low valuations, good transaction liquidity, and stable financial performance. This study uses secondary data in the form of financial reports and quarterly closing stock prices, with a total sample of 30 companies. The analysis method used is panel data regression with the Fixed Effect Model (FEM) approach. The results show that only the Price to Book Value (PBV) variable has a significant effect on stock prices. Meanwhile, the PER, ROA, and ROE variables did not have a significant effect on stock prices during the research period. These findings indicate that investors in this index consider valuation indicators such as PBV more than profitability or profit growth ratios. Overall, this study contributes to the understanding of the factors that determine stock prices in the value stock group in the Indonesian capital market.